Exploring the Relationships Between the Farmers Farm Expenses, Land Size, and Sugarcane Yield: Evidence from the Philippines - Paulino A Oñal, Jr.; Bro. Jian Meng Yuan; Paulino Miguel M. Oñal (Future Science / FSH-PH Publications, 2026)
Sugarcane (Saccharum officinarum, L.) is a perennial plant in the Poaceae family. In the Philippines, the industry is a major dollar source of income, contributing around Php 70 billion annually. The study aims to investigate the relationships between landholding size, average farm expenses, and sugarcane production volume in the Philippines. Employed in this study is the descriptive-correlation method. The instrument used was the validated survey questionnaire which is designed for correlating farmers’ expenses, land size as well as the yield of sugarcane. The 320 sugarcane farmers were randomly identified at the seven locations in the Visayas area of the Philippines. Results indicate that the majority of the area is small (69.7%), with a very high expense (38.4%) and low production (53.9%) of <49 TC/ha. Analysis of variance (ANOVA) implied that there’s a significant difference in the production of sugarcane among the different locations in the Philippines. Furthermore, results implied that the size of landholdings and average farm expenses significantly influence the production (alpha = 0.01). Relatively, the landholding size and average farm expenses strongly correlate with the volume of production (alpha = 0.01). The economies of scale are a very crucial parameter in the sugarcane growing business. The size of landholding and average expense have a direct contribution to the level of production. The government should now re-evaluate programs and projects related to downsizing farmers’ area and subsidizing farm operations. Review of policy to support the sugarcane farmer in terms of financing and land distribution should be done immediately.